Peran Scrubber Pada Bahan Bakar Rendah Sulfur Dalam Mengatasi Polusi Udara Maritim - Hutajulu, Solafide; Aprilla, Rabena; Pardi, Hilfi (Politeknik Bumi Akpelni, 2023)
This device, called a Scrubber, is a solution to overcome air pollution resulting from the performance of ship fuel. This machine's process requires indicator media in the form of seawater and fresh water, where this indicator is only used in certain situations and conditions. This research aims to find out and identify the role of scrubbers on low sulfur fuel in dealing with air pollution in maritime areas. This research uses a qualitative approach with a literature review method. As a result, this scrubber provides efficient results by converting fuel containing SO2 into environmentally friendly fuel due to the role of indicators, which are processed simultaneously in the scrubber. However, this machine has advantages and disadvantages that are of concern to scrubber users. Therefore, supervision and skills in understanding the application of scrubbers are needed so that they can provide excellent and efficient results.